Pengaruh Price Discount dan Konsep Diri terhadap Keputusan Pembelian Produk Skintific pada Tiktok Shop - Inas Rahmania; Abdul Waris (Lembaga Pengembangan Kinerja Dosen, 2024)
Companies are competing to develop their products to be in demand by consumers amidst the rapid development of the beauty industry. One of them is by providing price discounts and adjusting the concept carried with the self-concept owned by consumers. This research aims to determine the effect of price discounts and self-concept on purchasing decisions for Skintific products on Tiktok Shop. The research used is quantitative research with variables of price discount, self-concept, and purchasing decisions. By using data collection techniques in the form of questionnaires and documentation and using purposive random sampling techniques with a total of 100 respondents who use Skintific products. Data analysis uses validity tests, reliability tests, descriptive analysis, classical assumption tests, and hypothesis tests. The results of this research explain that price discounts and self-concept have a positive and significant impact on purchasing decisions both partially and simultaneously. That way, Skintific can maintain price discounts by providing relatively the same discounts on its products. On the other hand, self-concept can be improved so that consumers feel interested in Skintific products